Principal Implementation In Managing Conflict In The Educational Environment - Ahmed Hossein (CV Edujavare Publishing, 2024)
Conflict is an inevitable phenomenon in educational institutions due to differences in values, interests, perceptions, communication styles, and organizational goals among stakeholders. The principal plays a strategic role in managing conflicts effectively to maintain a conducive learning environment and ensure institutional effectiveness. This study aims to examine the implementation of principals' leadership in managing conflict within educational settings and its impact on organizational performance, teacher collaboration, and school climate. Employing a qualitative literature review approach, this research analyzes scholarly articles, educational management theories, and empirical studies related to conflict management in schools. The findings indicate that successful principals utilize various conflict management strategies, including collaboration, negotiation, mediation, effective communication, and participatory decision-making. Transformational and instructional leadership approaches significantly contribute to reducing interpersonal tensions and fostering a culture of trust and cooperation. Furthermore, principals who demonstrate emotional intelligence and organizational competence are more capable of addressing conflicts constructively. Effective conflict management not only minimizes disruptions but also promotes professional growth, organizational learning, and educational quality improvement. Therefore, principals must develop comprehensive conflict management competencies to navigate complex educational challenges and support sustainable school development.